Intestinal necrosis: A devastating complication of nephrotic syndrome - M.J. Human; N. Tshifularo (Elsevier, 2022)
Nephrotic syndrome (NS) is a protein-losing enteropathy that can present as a surgical emergency or complicate routine surgical procedures. This case highlighted the hypercoagulable state that resulted in significant small bowel ischaemia and necrosis. Mesenteric ischaemia as a complication of NS has not been reported in the paediatric population. The postoperative overwhelming sepsis also highlighted the effect of impaired immunity in NS on patient outcomes.